THE INFLUENCE OF ORGANIZATIONAL CULTURE AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE PRODUCTIVITY OF PT PELABUHAN TANJUNG PRIOK PALEMBANG BRANCH - Sari, Sindang (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2025)
This study aims to assess the effect of organizational culture and commitment on employee productivity at PT Pelabuhan Tanjung Priok's Palembang branch. Questionnaires were distributed to 62 employees, and both quantitative and qualitative descriptive methods were employed to analyze the data from primary and secondary sources. The findings indicate that neither organizational culture nor organizational commitment significantly influence employee productivity. This conclusion is drawn from the rejection of H0 and acceptance of H1, as Fcount (0.578) is less than Ftable (0.250). Additionally, the F test shows a significance value of 0.567, which is greater than 0.05, confirming that the independent variables (organizational culture and commitment) have no significant impact on the dependent variable (employee productivity).